Climate Change and Arctic Shipping Futures: Community Perspectives on the State of Shipping and Emergency Preparedness in Canada’s Northwest Passage - Yaremko, Jeffrey (Université d'Ottawa | University of Ottawa, 2024)
Shipping trends in the Canadian Arctic are projected to continue along a rising trajectory due to a warming climate, loss in sea ice extent, and growing economic interests in the region. This is resulting in global interest in the region and potential for Arctic shipping routes, notably the Northwest Passage (NWP). As Arctic shipping traffic continues to rapidly grow in Canada, questions arise about the preparedness of both coastal communities and government in the event of a shipping accident, or a worst-case scenario shipping disaster. This thesis aims to integrate the perspectives of residents from Pond Inlet, Nunavut, a coastal community that sits along the entranceway/exit of the NWP and is at-risk of experiencing a shipping accident in the region. A review of literature and relevant grey literature (i.e. acts, agreements, reports) was undertaken to ground the study in current research and policy. A survey with a quantitative and qualitative approach was implemented to document the perspectives of Pond Inlet residents, verifying and identifying changes in shipping patterns in the region and exploring shipping futures around the community. This also entailed acquiring an understanding of how residents perceived shipping accidents, worst-case scenarios, and emergency preparedness for their community and the region. This study contributes to current understandings and research on the state of Arctic shipping and emergency preparedness from the perspectives of coastal communities in the region.
Keywords: Arctic; Shipping Accidents; Marine Disasters; Emergency Preparedness; National Security; Community-based research; Coastal community perspectives; Climate Change Adaptations